2021
DOI: 10.1111/inm.12962
|View full text |Cite
|
Sign up to set email alerts
|

‘Are they really allowed to treat me like that?’ – A qualitative study to explore the nature of formal patient complaints about mental healthcare services in Sweden

Abstract: The improvement of mental healthcare services requires patients' experiences to identify problems and possible deficits in care. In this study, we explored the nature and meaning of formal patient complaints about mental healthcare services in one region of Sweden using a descriptive design with a qualitative approach. A systematic random sample of 106 formal patient complaints about mental healthcare services in 1 Swedish county was selected and analysed thematically, based on descriptive phenomenology. Theme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(20 citation statements)
references
References 27 publications
(56 reference statements)
0
20
0
Order By: Relevance
“…Ten studies reported being a descriptive, qualitative, or descriptive qualitative study ‘with’ or ‘grounded in’ a phenomenological approach. Although seven studies reported adopting a qualitative or descriptive qualitative approach, they proceeded to describe a descriptive phenomenological data analysis technique by Giorgi, Colaizzi or Sundler (Al Gilani et al, 2021; Macapagal et al, 2021; Nuuyoma & Makhene, 2021; Olander et al, 2021; Othman et al, 2021; Ratnawati & Rizaldi, 2021; Sundler et al, 2021). However, one study (George et al, 2021) used a ‘phenomenological approach with descriptive thematic analysis’ without providing references.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten studies reported being a descriptive, qualitative, or descriptive qualitative study ‘with’ or ‘grounded in’ a phenomenological approach. Although seven studies reported adopting a qualitative or descriptive qualitative approach, they proceeded to describe a descriptive phenomenological data analysis technique by Giorgi, Colaizzi or Sundler (Al Gilani et al, 2021; Macapagal et al, 2021; Nuuyoma & Makhene, 2021; Olander et al, 2021; Othman et al, 2021; Ratnawati & Rizaldi, 2021; Sundler et al, 2021). However, one study (George et al, 2021) used a ‘phenomenological approach with descriptive thematic analysis’ without providing references.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies had multiple data collection methods such as a combination of individual and dyadic interviews (Olander et al, 2021), or individual interviews and focus groups (Mathews & Anderson, 2021; Othman et al, 2021). Other online data collection methods included open‐ended questionnaires (Vignato et al, 2021), written narrative reflective inquiry (Schuler et al, 2021), written complaints documented in a report (Sundler et al, 2021), written descriptions and illustrative examples (Aldiabat et al, 2021) sent through email.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sometimes, patients experienced they received contradicting information (Eriksson & Svedlund, 2007; Jangland et al, 2009; Kee et al, 2018; Olsson, 2016; Sundler et al, 2022; Wofford et al, 2004). It was especially confusing when such contradicting information came from different health care professionals (Sundler et al, 2022; Wofford et al, 2004), as one patient observed:
One doctor will come in and say they are going to do one thing and someone will come in later and say they're going to do something else […] It seems the left hand doesn't know what the right hand is doing. (Wofford et al, 2004, p. 137)
…”
Section: Resultsmentioning
confidence: 99%
“…TA B L E 1 (Continued) not updated about the patients' health (Jangland et al, 2009;Olsson, 2016). Patients felt lost in a system where they did not know what comes next and had no idea who was responsible for them (Hågensen et al, 2018;Olsson, 2016;Sundler et al, 2022), resulting in poor follow-up and delays (Jangland et al, 2009;Ming et al, 2019;Råberus et al, 2018;Sundler et al, 2020Sundler et al, , 2022Wofford et al, 2004). One relative could not understand why his father had to wait so long for treatment:…”
Section: Problems With Access To Health Care Services-fighting Their ...mentioning
confidence: 99%